Case report: Hematologic malignancies concomitant diagnosis of hairy cell leukemia and chronic lymphocytic leukemia: A rare association - Valvano, Luciana; D’Auria, Fiorella; Grieco, Vitina; Statuto, Teodora; Nozza, Filomena; Pietrantuono, Giuseppe; Villani, Oreste; D’Arena, Giovanni; Lamorte, Daniela (Frontiers in Oncology, 2022)
A case of concomitant hairy cell leukemia (HCL) and chronic lymphocytic leukemia (CLL) in a 50- year-old man was reported. Flow cytometry and droplet digital PCR (ddPCR) were used to detect the B-Raf proto-oncogene (BRAF) V600E mutation. The HCL population was the predominant component. The patient was first treated with cladribine and then with rituximab and achieved HCL partial remission. Importantly, the high sensitivity of our flow cytometric approach allowed the detection of a small population “P3,” in addition to the typical HCL and CLL clones. The P3 clone changed over time, from an HCL-like to a CLL-like immunophenotype. This case is added to the few other cases of synchronous HCL and CLL already reported in the literature and underlines the importance of analyzing chronic lymphoproliferative disorders by highly sensitive diagnostic techniques, like the multicolor flow cytometry and ddPCR, to evaluate the possible association between HCL and CLL at diagnosis.